Developmental social vulnerability as the intrinsic origin of psychopathology: A paradigm shift from disease entities to psychiatric derivatives within human diversity - Morioka, Hirofumi; Ijichi, Shinji; Ijichi, Naomi; Ijichi, Yukina; King, Bryan H. (Medical Hypotheses, 2019)
How a social episode is perceived by a person and how the experience affects her/his subsequent behaviors will inevitably and sometimes accidentally vary in each case on the developmental trajectory from the birth of consciousness to death. Both the preceding developmental conditions and the social impact of the episode become a starting point for the following states of human complex conditions, creating the extraordinary diversity that characterizes our complex society. In this evolutionarily carved landscape, genetic factors including stochastic epistasis, environmental modification, and gene-environment interactions are all active. In these processes, interactions between developmental social vulnerability and environmental influences can lead to the emergence and persistence of some derivative states with social maladaptation. In our model, every psychiatric condition including aberrant paranoid-hallucinatory states is classified as a derivative state. The probability distribution curve for these derivative states has a non-linear relationship with the liability in the population, and there is none with probability 1.0 or zero. Individuals with trivial social vulnerability or high resilience may develop the derivative states in tremendously stressful circumstances, and individuals with huge social vulnerability may not necessarily develop the derivative states in the presence of adequate social supports. Social skillfulness/unskillfulness and behavioral flexibility/inflexibility form the core of the vulnerability-related dimensions. The clinical picture of a derivative manifestation is profiled depending on the individual trait levels in the derivative-related dimensions. Each derivative state has a requisite lineup of dimensions and each dimension can contribute to multiple psychiatric conditions. For example, aberrant paranoid-hallucinatory states and bipolar condition may share some developmental conditions as the derivative-related dimensions. Therefore, multiple derivative states can co-occur or be sequentially comorbid. Although the ‘learned strategies’ can ostensibly mask the clinical manifestation of developmental deviations, the change of the true dimensional position to the socially skillful direction is efficiently obtained through social experiences in a supportive environment. The liability-probability model makes it impossible to discriminate individuals with psychiatric diagnosis from individuals without the diagnosis and allows all of us to reside in the same human complex diversity.